An alternative in situ gel-formulation of levofloxacin eye drops for prolong ocular retention - Himanshu Gupta; M Aqil; R K Khar; Asgar Ali; Aseem Bhatnagar; Gaurav Mittal (Wolters Kluwer Medknow Publications, 2015)
Introduction: Delivering drugs to ocular region is a challenging task. Eye physiological barriers lead to relatively less therapeutic and bioavailability effect by the conventional eye drops. This may be overcome by the use of in situ gel delivery system. Objective: The objective of our work was to formulate an ocular delivery system of levofloxacin, based on the concept of ion (sodium alginate) and pH (chitosan) activated in situ gelation concept. Due to its elastic properties, in situ gels resist the ocular drainage of drug leading to longer contact times with ocular surface. Materials and Methods: The formulation was evaluated for physicochemical characteristics, in vitro drug release. Ocular retention studies were carried out by Gamma scintigraphy. Time activity curve was plotted between marketed formulation and developed formulation for comparing drug drainage from the eye with time. Ocular tolerance test was performed by handheld infra-red camera. Results and Discussion: The formulations showed a first-order release pattern over 12 h. Both in vitro release studies and in vivo gamma scintigraphy precorneal retention studies indicated better therapeutic efficacy compared with standard eye drops. Conclusion: The results demonstrated that the developed in situ gel of levofloxacin is nonirritant, has prolonged action and is a better option in terms of retention, ocular bioavailability and patient compliance when compared with plain eye drops formulation.